DNA vaccine protection against SARS-CoV-2 in rhesus macaques - Yu, Jingyou; Tostanoski, Lisa H.; Peter, Lauren; Mercado, Noe B.; McMahan, Katherine; Mahrokhian, Shant H.; Nkolola, Joseph P.; Liu, Jinyan; Li, Zhenfeng; Chandrashekar, Abishek; Martinez, David R.; Loos, Carolin; et al. (Science (American Association for the Advancement of Science), 2020)
The development of a vaccine to protect against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an urgent biomedical need. Yu et al. designed a series of prototype DNA vaccines against the SARS-CoV-2 spike protein, which is used by the virus to bind and invade human cells. Analysis of the vaccine candidates in rhesus macaques showed that animals developed protective humoral and cellular immune responses when challenged with the virus. Neutralizing antibody titers were also observed at levels similar to those seen in humans who have recovered from SARS-CoV-2 infection. Science , this issue p. 806 Successful protection against SARS-CoV-2 in rhesus macaques by means of a prototype DNA vaccine is described. The global coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has made the development of a vaccine a top biomedical priority. In this study, we developed a series of DNA vaccine candidates expressing different forms of the SARS-CoV-2 spike (S) protein and evaluated them in 35 rhesus macaques. Vaccinated animals developed humoral and cellular immune responses, including neutralizing antibody titers at levels comparable to those found in convalescent humans and macaques infected with SARS-CoV-2. After vaccination, all animals were challenged with SARS-CoV-2, and the vaccine encoding the full-length S protein resulted in >3.1 and >3.7 log 10 reductions in median viral loads in bronchoalveolar lavage and nasal mucosa, respectively, as compared with viral loads in sham controls. Vaccine-elicited neutralizing antibody titers correlated with protective efficacy, suggesting an immune correlate of protection. These data demonstrate vaccine protection against SARS-CoV-2 in nonhuman primates.